INTERPRETASI POTENSI EKOWISATA DUSUN DAROK KECAMATAN BONTI KABUPATEN SANGGAU KALIMANTAN BARAT - Islamiati, Resti; Kartikawati, Siti Masitoh; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2020)
Darok hamlet is located in the bonti sub district of sanggau district. Has many tributaries such as the Hisi, river the Himua and Tangis, the Darok and the Bonti river. Darok hamlet has good natural forest. Has the status of protected forest areas Mount Budu, Iron Mountain, there are protected plants Amorphophallus titanium dan Rafflesia tuan mudaee young master one of West Kalimantan endemic. There are animals like tringgiling, jungle cats, and proboscis mongkeys which are still widely around the river. Darok village is also still thick with ‘Gawai’ traditions. The purpose of ths study was to record the potential of ecotourism and develop interpretations of the ecotourism potential of the village of Darok. The method used is exploration and ascending coordinates and direct interviews with hamlet heads, custom temenggung and local communities. The results of explroration there are 28 attractions that can support the interpretation of ecotourism potential, namely 18 physical potentials, 3 potential rare and endemic plants, 7 culture potentials. The results of the exploration were develoved into two tour package pathways, namely the protected forest path package and social culture this package was made based on field research. The protected forest package is on the heavy side, the settlement is 3 km away, there are potential waterfalls cascades, cascade amorphophallus titanium and others. While the social culture route in the north is 1 km away there is potential for tembawang forest, rice fields, traditional houses, and othersKeywords: Ecotourism, Interpretation, Pathway Interpretation.